2017
DOI: 10.1016/j.stemcr.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Schwann Cells in the Ventral Dermis Do Not Derive from Myf5-Expressing Precursors

Abstract: SummaryThe embryonic origin of lineage precursors of the trunk dermis is somewhat controversial. Precursor cells traced by Myf5 and Twist2 (Dermo1) promoter activation (i.e., cells of presumed dermomyotomal lineage) have been reported to generate Schwann cells. On the other hand, abundant data demonstrate that dermal Schwann cells derive from the neural crest. This is relevant because dermal precursors give rise to neural lineages, and multilineage differentiation potential qualifies them as adult stem cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Terminal Schwann cells could also behave as bona fide dermal stem cells. Gresset et al [ 23 ] and Iribar et al [ 24 ] also revealed the existence of the stem cell-like populations within adult neural crest cells in the skin, which could also be cultured as floating spheres. Generally speaking, these results suggest that spheres obtained from floating culture are actually a complex mixture of diverse cells, including stem, precursor, and terminally differentiated cells, while it is still unclear to what extent to which the diversity affected the biotechnological applications of hSKPs.…”
Section: What Are Hskps?mentioning
confidence: 99%
See 1 more Smart Citation
“…Terminal Schwann cells could also behave as bona fide dermal stem cells. Gresset et al [ 23 ] and Iribar et al [ 24 ] also revealed the existence of the stem cell-like populations within adult neural crest cells in the skin, which could also be cultured as floating spheres. Generally speaking, these results suggest that spheres obtained from floating culture are actually a complex mixture of diverse cells, including stem, precursor, and terminally differentiated cells, while it is still unclear to what extent to which the diversity affected the biotechnological applications of hSKPs.…”
Section: What Are Hskps?mentioning
confidence: 99%
“…Moreover, in the trunk skin, spheres presenting neural crest stem cell-like properties were restricted to the glial and melanocyte lineages rather than mesenchymal origination [ 42 ]. Another two recent studies provided further evidence to support that neurogenic potential detected in the sphere culture was ascribed to the neural crest-derived population of the Schwann cell lineage instead of dermal multipotent precursors [ 23 , 24 ]. Together, these data challenged the hypothesis whether hSKPs reflected an endogenous precursor with multipotent potential, as neural lineages were suggested to arise from neural-derived Schwann cells.…”
Section: Where Do Hskps Originate and Locate?mentioning
confidence: 99%
“…Historically, SKP were thought to represent a single multipotent dermal precursor cell type with multilineage differentiation capacity [2,[7][8][9][10], but research by Izeta and colleagues has shown that SKP actually represent a heterogeneous group of dermal precursor cells [11]. SKP are of particular interest for regenerative medicine as they share several properties with embryonic neural crest-derived stem cells, a group of highly plastic cells with unique properties that reside within the developing embryo [2,12,13]. In particular, we and others have shown that SKP are able to generate (1) neuronal cells such as Schwann cells [7,14,15], catecholaminergic [16], dopaminergic [17] and enteric [18] neurons, (2) mesodermal cell types including adipocytes, chondrocytes, osteocytes [2] and vascular smooth muscle cells [19] and (3) endodermal progeny such as hepatic cells [5,9,20,21] and islet-like insulin-producing cells [22].…”
Section: Introductionmentioning
confidence: 99%
“…[8] Moreover, previous research has indicated that these Myf5-derived cells can generate a functional neural crest cell type, [9] despite it is still under controversy. [10] The activity MRFs is tightly coupled to cell cycle control, and abnormal regulation of cell cycle can induce an uncontrolled myogenic differentiation. The retinoblastoma tumor suppressor protein (Rb) plays a key role in controlling cell cycle progression, and Rb-deficient mice exhibit high rates of apoptosis and an almost complete absence of myofibers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Moreover, previous research has indicated that these Myf5‐derived cells can generate a functional neural crest cell type, [ 9 ] despite it is still under controversy. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%